Contributions to the study of the Ethiopian Lepidoptera. I. The genus Melittia Hübner, 1819 [“1816”] (Lepidoptera: Sesiidae) with description of a new species - Gorbunov, Oleg G. (Zootaxa, 2015)
The genus Melittia Hübner, 1819 [“1816”] (Sesiidae) is reviewed for the country of Ethiopia. Melittia ambo sp. nov. is described from vicinities of Ambo, West Shewa zone, Oromia. Adults, including male and female genitalia, and the larval host plant, Citrullus colocynthis (L.) Schrad. (Cucurbitaceae), are illustrated. Additional, Melittia pyropis Hampson, 1919 is recorded for Ethiopia for the first time, and the holotype of M. abyssiniensis Hampson, 1919 is illustrated.